HISTOPATHOLOGICAL CHANGES IN GILLS AND OVARIES OF THE FRESHWATER PRAWN MACROBRACHIUM IDAE (HELLER) EXPOSED TO TEXTILE-MILL EFFLUENT - XAVIER, A. SILUVAI ANTONY; HANIFFA, M.A.; SOUZA, STEPHENT DE; ., S.J (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
Freshwater prawn, Macrobrachium idae were exposed to sublethal concentrations of textile-mill effluent. In the effluent exposed prawn the distal portion of the gill filament was congested with haemocytes showing necrosis. The follicular epithelium carrying oocyte became irregular and oocytes lost their characteristic shapes. Oocytes showed at resia with disappearance of nucleoli and nucleolar material.